Explanining the vigor (relative and absolute) in seeds: the biological meaning behind the mathematician (Bioscience Journal, 2020)
Seed vigor is the totality of all properties that determine a rapid and uniform emergence and development of normal seedling under a wide range of conditions. However, the physiological quality within a seed lot is not  homogeneous, generating a quality gradient between seeds. Thus, the vigor expressed by the final percentage of normal seedlings tends to underestimate the quality of the batch, considering the total number of seeds. One possible method for correcting such an effect would be to weight vigor by germination, generating an index called relative vigor. The index reflects the “success” of viable seeds in maintaining their potential under stress. In this context, this review article proposes the possibility of using a new measure for vigor and new interpretation of relative vigor, as well as providing the mathematical basis for its use.